2020
DOI: 10.1136/bmjspcare-2020-002630
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare trajectories and costs in the last year of life: a retrospective primary care and hospital analysis

Abstract: ObjectivesTo analyse healthcare utilisation and costs in the last year of life in England, and to study variation by cause of death, region of patient residence and socioeconomic status.MethodsThis is a retrospective cohort study. Individuals aged 60 years and over (N=108 510) who died in England between 2010 and 2017 were included in the study.ResultsHealthcare utilisation and costs in the last year of life increased with proximity to death, particularly in the last month of life. The mean total costs were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…20 The present study was conducted in parallel with a study of end-of-life healthcare trajectories and costs for decedents in England during 2010-2017. 21 We describe the rationale for separating the two studies in the Discussion section.…”
Section: What Is Their Significance?mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The present study was conducted in parallel with a study of end-of-life healthcare trajectories and costs for decedents in England during 2010-2017. 21 We describe the rationale for separating the two studies in the Discussion section.…”
Section: What Is Their Significance?mentioning
confidence: 99%
“…Our parallel study of decedents in England was able to draw on primary care data, although only for a particular cohort. 21…”
Section: Main Findingsmentioning
confidence: 99%
“…The costs for general healthcare in the elderly has been found to increase with proximity to death, and has been associated with sex [ 2 , 3 , 4 ], place of living [ 1 , 4 , 5 ], SES [ 6 ] or age, as described [ 2 , 4 , 7 , 8 ]. In the present evaluation, we assessed costs for dental services provided to the very old by one statutory insurer in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with medical costs throughout most of the life course, end-of-life costs have been found to be high, mainly driven by repeated inpatient (hospital) admissions [ 1 ]. Costs have been associated with aspects like sex (with ambiguous data finding either male or female individuals experiencing higher medical costs towards the end of life) [ 2 , 3 , 4 ], the place of living (with costs being higher in more urban and affluent areas) [ 1 , 4 , 5 ], socio-economic status (SES, with costs being higher in more affluent high-SES groups) [ 6 ] or age (with end-of-life costs being consistently higher in younger-dying individuals than those dying older) [ 2 , 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 34 Thus, several studies have tried to examine whether the concept of end-of-life illness trajectories can be ascertained in real-life data. [35][36][37][38][39][40][41] Teno et al, Lunney et al and Stolz et al conducted studies measuring functional decline at the end of life, and all concluded that the underlying illness causing death was following the pattern of illness trajectories as suggested by Glaser and Strauss. 11 35-38 Contrary to this, in 2007, Gott et al examined illness trajectories of physical function experienced by patients with heart failure prior to death but discovered no typical heart failure trajectory for most of the patients included.…”
Section: Open Accessmentioning
confidence: 99%